If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6x+8)/(4)=2x+5
We move all terms to the left:
(6x+8)/(4)-(2x+5)=0
We get rid of parentheses
(6x+8)/4-2x-5=0
We multiply all the terms by the denominator
(6x+8)-2x*4-5*4=0
We add all the numbers together, and all the variables
(6x+8)-2x*4-20=0
Wy multiply elements
(6x+8)-8x-20=0
We get rid of parentheses
6x-8x+8-20=0
We add all the numbers together, and all the variables
-2x-12=0
We move all terms containing x to the left, all other terms to the right
-2x=12
x=12/-2
x=-6
| h=18+5h÷7 | | -9(3x-1)-4(7x+2)=8 | | 2(4y+8)=40 | | 100(t)=-16t^2+120t | | 3x(2x-5)(6x+7)=0 | | 3n(3n+3)=0 | | 5(x-3)-2x=8 | | 285-y=160 | | 146=-v+198 | | 173=-x+95 | | 72-v=182 | | x−3/11=8 | | x−311=8 | | 2(3k+8)=50+5k | | 4w+12=5w+9 | | .25x+.1(15-x)=15(.19) | | 57.6r+23.23=2.14 | | -3=1/15x | | 9g-8g=19 | | 1-11x=123 | | 20+6w=10w | | 22=x/5+14 | | 8x-15×=-44-12 | | 357+0.02x=140+0.09x | | 3x+8=-5x+1 | | 6x+90=120 | | (3k+2)^2=49 | | 90-x=59 | | 4(2x-3)6x=2 | | X²-8x=96 | | 2(2x-3)+3(5-x)=1ï | | 4^2x+1=0.25 |